How β-cyclodextrin- loaded mesoporous SiO2 nanospheres ensure efficient adsorption of rifampicin - Sun, Xun; Chen, Mingming; Lei, Jiayu; Liu, Xinran; Ke, Xin; Liu, Wengang; Wang, Jingkuan; Gao, Xiaodan; Liu, Xin; Zhang, Yun (Frontiers in Chemistry, 2022)
Abstract: In this study, β-cyclodextrin (β-CD) was loaded by an in situ synthesis method, β-CD@mesoporous SiO2 nanospheres (β-CD@mSi) with a monomer diameter of about 150 nm were prepared. The loading of β-CD reduces the specific surface area of mesoporous SiO2 nanospheres (mSi) and enhances the adsorption effect. When the temperature is 298 k, the removal efficiency of 100 mg/L rifampicin solution can reach 90%, and the adsorption capacity was 275.42 mg•g−1 at high concentration. Through the calculation and analysis of adsorption kinetics, adsorption isotherms and adsorption thermodynamics based on the experimental data, the reaction is a spontaneous endothermic reaction dominated by chemical adsorption. The electron transfer pathway, structure–activity relationship and energy between β-CD and rifampicin were investigated by quantum chemical calculations. The accuracy of the characterization test results to judge the adsorption mechanism was verified, to show the process of rifampicin removal by β-CD@mSi more clearly and convincingly. The simulation results show that π–π interaction plays a major interaction in the reaction process, followed by intermolecular hydrogen bonding and electrostatic interactions.